2023
DOI: 10.3390/v15051143
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Functional Tradeoffs between Protein Stability and ACE2 Binding in the SARS-CoV-2 Omicron BA.2, BA.2.75 and XBB Lineages: Dynamics-Based Network Models Reveal Epistatic Effects Modulating Compensatory Dynamic and Energetic Changes

Abstract: Evolutionary and functional studies suggested that the emergence of the Omicron variants can be determined by multiple fitness trade-offs including the immune escape, binding affinity for ACE2, conformational plasticity, protein stability and allosteric modulation. In this study, we systematically characterize conformational dynamics, structural stability and binding affinities of the SARS-CoV-2 Spike Omicron complexes with the host receptor ACE2 for BA.2, BA.2.75, XBB.1 and XBB.1.5 variants. We combined multi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 147 publications
(256 reference statements)
0
23
0
Order By: Relevance
“…133,134 The adaptation of this approach for the analysis of rigid and flexible residues in the SARS-CoV-2 S proteins was detailed in our previous studies. 83 In this approach, the high values of distance fluctuation stability indexes point to structurally rigid residues as they display small fluctuations in their distances to all other residues, while small values of this index would point to more flexible sites that display larger deviations of their inter-residue distances. A comparative analysis of the residuebased distance fluctuation profiles revealed several dominant and common peaks reflecting the similarity of the topological and dynamical features of the RBD-ACE2 complexes (Supporting Materials, Figure S4).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…133,134 The adaptation of this approach for the analysis of rigid and flexible residues in the SARS-CoV-2 S proteins was detailed in our previous studies. 83 In this approach, the high values of distance fluctuation stability indexes point to structurally rigid residues as they display small fluctuations in their distances to all other residues, while small values of this index would point to more flexible sites that display larger deviations of their inter-residue distances. A comparative analysis of the residuebased distance fluctuation profiles revealed several dominant and common peaks reflecting the similarity of the topological and dynamical features of the RBD-ACE2 complexes (Supporting Materials, Figure S4).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…82 By combining atomistic simulations and a community-based network model of epistatic couplings, we found that convergent Omicron mutations such as G446S (BA.2.75, BA.2.75.2, XBB), F486V (BA.4, BA.5, BQ.1, BQ.1.1), F486S, F490S (XBB.1), F486P (XBB.1.5) can display epistatic relationships with the major stability and binding affinity hotspots which may allow for the observed broad antibody resistance. 83 In the current study, we perform multiple microsecond MD simulations and Markov state model (MSM) analysis to characterize conformational landscapes and identify specific dynamic signatures of the SARS-CoV-2 S RBD-ACE2 complexes for the recently emerged XBB.1, XBB.1.5, BQ.1, and BQ.1.1 Omicron variants. The results of simulations and MSM analysis provide a detailed characterization of the conformational states in the Omicron complexes, showing the increased thermodynamic stabilization of the XBB.1.5 complex, which is contrasted to more dynamic BQ.1 and BQ.1.1 variants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…By applying mutations of protein residues, we compute dynamic couplings of residues and changes in the short path betweenness centrality (SPC), and the average short path length (ASPL) averaged over all modifications in a given position. The details of this approach were described in our recent studies 72,77,78 Here, we briefly outlined the key elements of this approach. The change of SPC or ASPL upon mutational changes of each node is done by systematically removing nodes from the network.Δ L i = 〈‖Δ L node i ( j )‖ 2 〉where i is a given site, j is a mutation and 〈⋯〉 denotes averaging over mutations.…”
Section: Methodsmentioning
confidence: 99%
“…We complemented the PRS results with the network-based mutational profiling of allosteric residue propensities 72,77,78 that are computed using topological network parameters SPC and ASPL (see Materials and Methods) and can characterize the effect of mutations on long-range interactions and global network of allosteric communications in the RBD-ACE2 complexes. Through ensemble-based averaging over mutation-induced changes in these network metrics, the proposed model can identify positions in which mutations on average cause network changes.…”
Section: Perturbation Response Scanning Reveals Variant-specific Modu...mentioning
confidence: 99%
See 1 more Smart Citation